Rotifera Abundance and Species Diversity in Al-Kufa River, Iraq (Global Journal of Science Frontier Research, 2017)
The present study was carried out on AL-Kufa River in the middle of Iraq to study the biodiversity of rotifera by investigating some of biodiversity index values. The samples were collected monthly, from March 2012 till February 2013, at four selected stations on the river; the first is located in Al-Kifil City, the second in Al-Kufa City, the third in AbuSkhar City and the fourth after Al-Mushkab City. About 92 Taxa of rotifera was identified. The rotifera density recorded ranged from 425 to 17925 Ind./m 3 , the high values were in Spring and Autumn, while the lowest values were recorded in Summer and Winter. The results of the relative abundance index showed that Keratella cochlearis, K. valga, Euchlanis delatata were more abundant in the Kufa River. Also the results of constancy index showed 9 taxa belonged to rotifera which were considered "Constant" at all stations. The other taxonomic units ranged between emergency and additive according to its presence in the study stations.
Keywords: biodiversity index values; density; constancy index; ecological stresses